From the guest editor - Odendaal, Nancy (Town and Regional Planning, 2012)
THEMATIC REFLECTIONS ON THE RELEVANCE OF PLANNING EDUCATION IN AFRICA: AN INTRODUCTION It is now a well-established fact that the future in Africa is urban. The United Nations Human Settlements Programme predicts that the increase in urban population in developing nations between 2007 and 2025 is projected to be 53 million, compared to 3 million in the developed world; 70% of the world’s population will live in cities by 2050, most of them in the Global South (United Nations Human Settlements Programme, 2009). Intervention in urban spaces in these regions needs to contend with the backlogs reflected in inadequate service infrastructure and housing backlogs, as well as rapid urbanisation within a context of climate change and global disparities in economic distribution. The form that urbanisation takes in Africa varies across regions and is substantially different from the evolution of the urban and regional planning profession in the early 1900s. It is a less predictable and more volatile which many policymakers on this continent find overwhelming and threatening (Pieterse, 2010). Intervention that assumes industrialisation, employment and the financial as well as institutional capacity to provide infrastructure is not effective. The conditions that inform change in African urban spaces need to be examined carefully.